Роль креативної моделі освіти у формуванні суспільства інноваційного розвитку в епоху технологічної революції 5.0 та глобалізації - Нікітенко, Віталіна Олександрівна (Національний технічний університет "Харківський політехнічний інститут", 2024)
Розглянуто трансформацію освіти в умовах інформаційного суспільства, яке водночас постає як «суспільство знань», цифрове суспільство чи смарт-суспільство, що вимагає формування інноваційних підходів до освіти, орієнтованих на розвиток креативної особистості та сприяння інноваційному прогресу. Визначено роль освіти як основи соціокультурного та економічного розвитку, адаптера до умов технологічної революції 5.0 і рушія змін. Доведено потребу у перепрофілюванні освітніх систем відповідно вимогам інноваційної економіки, що передбачає створення умов для формування у студентів не лише технічних навичок, а й критичного мислення, креативності та здатності адаптуватися до змінюваного світу. Розглянуто креативну модель освіти як стратегічний фактор розвитку інноваційного суспільства.

The transformation of education in the conditions of the information society, which at the same time appears as a "knowledge society", a digital society or a smart society, which requires the formation of innovative approaches to education, focused on the development of a creative personality and promoting innovative progress, is considered. The role of education as the basis of socio-cultural and economic development, an adapter to the conditions of the technological revolution 5.0 and a driver of change is determined. The need for repurposing educational systems in accordance with the requirements of the innovative economy is proven, which involves the creation of conditions for the formation of students not only technical skills, but also critical thinking, creativity and the ability to adapt to the changing world. The creative model of education is considered as a strategic factor in the development of an innovative society.
The role of creative model of education in the formation of a society of innovative development in the era of technological revolution 5.0 and globalisation
Keywords: креативна модель освіти; креативна особистість; технологічна революція 5.0; глобалізація 5.0; інноваційне суспільство; creative model of education; creative personality; technological revolution 5.0; globalisation 5.0; innovative society